PENGARUH BOARD DIVERSITY DAN FIRM SIZE TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH (BUS) TAHUN 2017-2023 - Priansyah, Dodi; Hafizi, Muhammad Riza; Hanafi, Ahmad; Misra, Isra (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to analyze the impact of board diversity and firm size on return on assets (ROA) in Islamic commercial banks in Indonesia from 2017 to 2023. Board diversity is measured by variables such as the percentage of women on the board, the average age of board members, and the education level of board members. Firm size is measured based on the total assets owned by the bank. The research method employed is multiple regression analysis using panel data consisting of annual reports of Islamic commercial banks registered with the Financial Services Authority (FSA) during 2017-2023. The research results indicate that board diversity, particularly the presence of women on the board, does not affect ROA. Additionally, the age of directors has a significant negative impact on ROA, while the education level of board members shows no effect on the bank's financial performance. Meanwhile, firm size has a considerable positive impact on ROA. This study contributes to the literature on corporate governance and financial performance in the Islamic banking sector by highlighting the significance of board diversity in enhancing financial performance.